Advancement in smart bone implants: the latest multifunctional strategies and synergistic mechanisms for tissue repair and regeneration - Shishuo Li; Zhentao Man; Kangqing Zuo; Linbo Zhang; Taixing Zhang; Guiyong Xiao; Yupeng Lu; Wei Li; Ningbo Li (Bioactive Materials, 2025)
Artificial implants have consistently been recognized as the most effective clinical strategy for repairing bone fractures and defects, particularly in orthopedics and stomatology. Nowadays, the focus of bone repair has shifted from basic fixation and structural restoration to the reconstruction of multifunctional “live” tissue to mimic the natural bone microenvironment. However, developing the smart implants with ideal osteogenesis-related multi-functions remains challenging, as the effects of physicochemical properties of implant materials on intracellular signaling, stem cell niches, and tissue regeneration are not yet fully understood. Herein, we systematically explore recent advancements in innovative strategies for bone repair and regeneration, revealing the significance of the smart implants that closely mimic the natural structure and function of bone tissue. Adaptation to patient-oriented osteogenic microenvironments, dynamic osteoblastogenesis-osteoclastogenesis balance, antibacterial/bactericidal capacity, vascularization, and osteoimmunomodulatory capacity and their regulatory mechanisms achieved by biomaterials design and functional modifications are thoroughly summarized and analyzed. Notably, the popular research on multifunctional platforms with synergetic interactions between different functions and treatment of complex clinical issues, including the emerging neurogenic bone repair, is also significantly discussed for developing more intelligent implants. By summarizing recent research efforts, this review proposes the latest multifunctional strategies and synergistic mechanisms of smart bone implants, aiming to provide better bone defect repair applications that more closely mimic the natural bone tissue.